DEVELOPMENT OF UNIQUE AND UNIVERSAL PROFESSIONAL COMPONENTS OF FUTURE ENGLISH LANGUAGE TEACHERS - Isamuxamedova Munisxon Najmitdinovna (Western European Studies, 2024)
An English teacher's skill set is the foundation of their capacity to motivate and instruct in the ever-changing field of education. Effective teachers possess a harmonious fusion of pedagogical knowledge, language proficiency, and compassionate communication. The field of teaching English is growing as time goes on, necessitating not only a thorough comprehension of conventional teaching techniques but also flexibility in the face of novel approaches and a variety of learning settings. To succeed in the changing educational environment and to help students develop a love of language and literature, English teachers must recognize the fundamental competencies of the profession.
Keywords: Components; professional development; technology; knowledge